2014
DOI: 10.3846/13923730.2014.937357
|View full text |Cite
|
Sign up to set email alerts
|

On the Solution of Energy Balance Equation System to Predict Temperature Distribution in the Building Elements With Ventilated Air Gap

Abstract: The article presents the solution of heat balance equation system, describing heat exchange processes in ventilated envelopes, which was applied to derive formulas for the calculation of temperatures in the ventilated layers of the envelopes. The accurateness of the formulas was assessed by experimental research and analysis of the calculation results. During the process of heat exchange balance equation solution, the equations were simplified by introducing the following restriction into the derived formulas:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Susanti et al demonstrate that due to various heat exchange process the temperatures of gaps may not be equated to the exterior temperature, especially in the case of double-skin roof [25]. The results of experimental research [26] demonstrated that the absolute error in the calculations of the average daily temperature of the ventilated air gap and external surface of the thermal insulation layer does not exceed the limits of 1.21 • C and 2.71 • C. The influence of doubleskinned structures on the energy performance of buildings is dealt with by experts all over the world, and some research is focused on climatic areas with temperate climates [27][28][29]. In this research, results of experimental heat measurements within the compositions of the monitored structures and the parameters of the internal and external environment were used in order to evaluate the influence of ventilated air gaps on the thermal technical behavior of lightweight timber-based cladding.…”
Section: Introductionmentioning
confidence: 99%
“…Susanti et al demonstrate that due to various heat exchange process the temperatures of gaps may not be equated to the exterior temperature, especially in the case of double-skin roof [25]. The results of experimental research [26] demonstrated that the absolute error in the calculations of the average daily temperature of the ventilated air gap and external surface of the thermal insulation layer does not exceed the limits of 1.21 • C and 2.71 • C. The influence of doubleskinned structures on the energy performance of buildings is dealt with by experts all over the world, and some research is focused on climatic areas with temperate climates [27][28][29]. In this research, results of experimental heat measurements within the compositions of the monitored structures and the parameters of the internal and external environment were used in order to evaluate the influence of ventilated air gaps on the thermal technical behavior of lightweight timber-based cladding.…”
Section: Introductionmentioning
confidence: 99%